THE ANALYSIS OF FREIGHT TRANSPORTATION COST OF SUPERIOR COMMODITIES IN EAST JAVA - -, Kariyoto (Accounting Department,, 2016)
Transport has a strategic role in the effort to support the development of Indonesia. Transportation directly affects the opening of opportunity leading to a wider market, on time delivery and price efficiency. The influence is not directly related to the multiplier effect which the price of commodities or services can go down and diversity of commodities can increase. The purpose of this study, to analyze the operational costs of freight transport suprior commodity in East Java. Qualitative research approach used to analyze the operational costs of freight transport, to Â identify the components of the cost of transport of goods using a landline as well as to analyze the contribution of freight vehicles operating costs of setting a selling price of superior commodity in East Java province. The results of the research that the operational costs of vehicles in Indonesia is higher compared to the average vehicle operating costs in the region. Vehicle operating costs in East Java is highly depend on the type of truck, tonnage transported. The highets costs in operating costs freight vehicles are fuel oil (BBM), depreciation costs and wage costs while the cost of driver salary while Â parts also highly influence on vehicle operating costs. The cost of fuel is influenced by the topography and road conditions of the route from Surabaya to Malang.Â